Digital literacy and farmers' non-farm employment-an empirical study based on CFPS - Shutong Li (Sustainable Futures)
The rapid development of the digital economy brings new opportunities for farmers' non-farm employment. Based on the China Family Panel Studies (CFPS) in 2014, 2016, and 2018, this paper constructs digital literacy evaluation indicators to empirically analyze the impact of digital literacy on farmers' non-farm employment. The study finds that: improving digital literacy can significantly promote farmers' non-farm employment, push farmers to achieve formalized and localized employment, and increase their wages; digital work literacy promotes farmers' non-farm employment more than digital learning, social, entertainment, and business literacy; enhanced digital literacy significantly promotes the participation in non-farm employment of the rural youth group, the highly educated, as well as the female and high-income level farmers; expanding social networks and enhancing social trust play an important mediating role in this process; the degree of digital infrastructure can moderate the relationship between digital literacy and non-farm employment. In the future, rural digital infrastructure should be strengthened, precise digital technology training should be provided to disadvantaged groups, and a good social trust environment should be created to promote non-farm employment for farmers.